(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The study -"Hidden Messages in Animated Films- Analytical Study" -aimed to identify the types of hidden messages used in animated films, and to reveal the strategies used in hidden messages used in animated films as well as to monitor the types of hidden political and religious messages، and social depending on the nature of the scene. It relied on the survey method, by analyzing the movie “The Pet Goat-2”, the animated film directed at adults. The researcher reached a set of results، the most important of which are: 1- The visible hidden messages are the most prominent hidden messages used in animated films. 2- The influential personality’s strategy is one of the most used strategies. 3- Most of the film’s hidden political messages considered America the main savior for all countries of the world. 4- Most of the film’s hidden religious messages had the main objective of distorting the symbols of the Christian and Islamic religions. 5-Most of the film’s hidden social messages aimed at implanting ideas of sexual suggestion, nudity, and violation of human rights into the subconscious.